Interaction-based information retrieval in multimodal, online, artefact-focused meeting recordings - Bouamrane, Matt-Mouley (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
Traditional search operations, topic detection or summarisation of meeting recordings are generally performed using segmentation and indexing techniques originally developed in the field of Multimedia Information Retrieval. However, many assumptions possible in a media production environment are often inadequate when applied to spontaneous meeting recordings, as features such as sudden changes in sound energy levels or high motion can be sparse or even inexistent in typical meetings. As a result, the dominant paradigm used for meeting browsing currently consists in performing text-based information retrieval operations on automatic speech recognition (ASR) transcripts. Meetings produce however another type of information not readily available in other multimedia recordings: interactions between participants. Although there is a growing interest in using this rich source of information, it remains difficult to harness due to the current limitations of (speech, gesture or higher-level action) recognition technologies. In computer-mediated online meetings, in which a space-based artefact (shared text or graphical document) acts as the focal point of the meeting, it is possible to generate metadata describing lowlevel actions of participants during the meeting. The semantics of these actions is many-fold: it is defined by the person who performed the actions, the nature, the content, the timing of these actions and finally the context (or target) of these actions. We explore a number of segmentation, indexing and search techniques specifically based on information collected about participants’ actions. We developed a temporal model in which navigation of meeting recordings is performed according to actions’content or actions’context. We investigate the relationships between the timing and content of actions and concurrent speech communications and if the temporal distance between the content of certain actions can be used as a reliable indication of semantic relatedness (topic) between these neighbouring actions. We explore visualisation of meeting information centred on the concept of data objects with persisting histories, rather than the more traditional Multimedia concept of media streams. A meeting browsing tool called the “Meeting Miner” was implemented. Evaluation of the Meeting Miner was performed through an analytic evaluation, a usability study, and a task-oriented information retrieval experiment. We complement the emerging Browser Evaluation Test (BET) framework with additional performance metrics. Results of our evaluation showed that interaction-based techniques incorporated into meeting browsing systems can indeed be used efficiently for navigating multimodal meeting recordings.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin